Modal Sosial dan Strategi Keberlangsungan Hidup Masyarakat Dayak Ngaju (Studi Kasus Pada Masyarakat Dayak Ngaju Desa Manusup di Kabupaten Kapuas Provinsi Kalimantan Tengah): Social Capital and Survival Strategy of Dayak Ngaju Community (Case Study on Dayak Ngaju Community manusup village in Kapuas Regency of Central Kalimantan Province) - Bahrianoor, Bahrianoor (Pencerah Publik, 2020)
This research discusses the role of social capital in fulfilling livelihood resources in Dayak ngaju indigenous communities in Central Kalimantan’s Manusup Village. This research is qualitative research with a descriptive design. The results of this study show that social capital has an important role and serves in expanding cooperation relationships, both relationships in social needs and relationships in the needs of livelihood sources.relationships in social needs serve to give birth to social solidarity formed through social institutions and religions. While the relationship in the needs of livelihood sources serves to support economic resilience by opening up interactions in strengthening mutually beneficial networks, both bonding, bridging, and linking capital. Bonding capital plays a role in forming togetherness and emotional connection and can strengthen internal relationships. Bridging capital can pave the way and stimulate community development. Meanwhile, linking capital brings great benefits to the progress of Manusup village, namely the advancement and development of potential expertise in obtaining livelihood sources.